Geosocial Networking Smartphone App Use and High-Risk Sexual Behaviors Among Men Who Have Sex With Men Attending University in China: Cross-sectional Study - Song Fan; Peiyang Li; Yuqing Hu; Hui Gong; Maohe Yu; Yi Ding; Zhenzhou Luo; Guohui Wu; Lin Ouyang; Huachun Zou (JMIR Publications, 2022)
BackgroundGay apps are smartphone-based geosocial networking apps where many men who have sex with men (MSM) socialize and seek sex partners. Existing studies showed that gay app use is associated with greater odds of high-risk sexual behaviors and potentially more HIV infections. However, little is known about this behavior among young MSM. ObjectiveWe conducted this study to understand gay app use and its influencing factors among MSM attending university in China. MethodsFrom January to March 2019, participants were recruited from 4 regions with large populations of college students in China: Chongqing, Guangdong, Shandong, and Tianjin. The eligibility criteria were MSM aged 16 years or older, self-identified as a university student, and being HIV negative. A self-administered online structured questionnaire was used to collect data on sociodemographic information, sexual behaviors, gay app use, substance use, and HIV testing history. We performed multivariable log-binomial regression to assess correlates of seeking sex partners via gay apps. ResultsA total of 447 MSM attending university with an average age of 20.4 (SD 1.5) years were recruited. Almost all participants (439/447, 98.2%) reported gay app use at some point in their life, and 240/439 (53.7%) reported ever seeking sex partners via gay apps. Blued (428/439, 97.5%) was the most popular gay app. Higher proportions of sexual risk behaviors (including seeking sex partners via apps [P<.001], engaging in group sex [P<.001], having multiple sex partners [P<.001], unawareness of sex partners' HIV status [P<.001], and using recreational drugs during sex [P<.02]) were positively associated with the increase in the frequency of gay app use. In multivariable analysis, participants who used gay apps to seek sex partners might be more likely to have multiple sex partners in the past 3 months (adjusted prevalence ratio [APR] 1.53, 95% CI 1.33-1.76; P<.001), engage in group sex in the past 3 months (APR 1.55, 95% CI 1.35-1.78; P<.001), and have sex partners with unknown or positive HIV status (APR 1.72, 95% CI 1.46-2.01; P<.001). ConclusionsSeeking sex partners via gay apps may associate with the increased high-risk sexual behaviors among MSM attending university. The causality between seeking sex partners via gay apps and increased high-risk sexual behaviors should be further investigated so as to inform potential policies for HIV prevention. Trial RegistrationChinese Clinical Trial Registry ChiCTR1900020645; http://www.chictr.org.cn/showprojen.aspx?proj=34741